Surgical Management of Encapsulating Peritoneal Sclerosis: A Case Report in Kidney Transplant Patient - R. Shahbazov; M. Talanian; J. L. Alejo; F. Azari; A. Agarwal; K. L. Brayman (Case Reports in Surgery)
Introduction. Encapsulating peritoneal sclerosis (EPS) is a clinical syndrome of progressive fibrotic change in response to prolonged, repetitive, and typically severe insult to the peritoneal mesothelium, often occurring in the setting of peritoneal dialysis (PD). Clear guidelines for successful management remain elusive. We describe the successful surgical management of EPS in a 28-year-old male s/p deceased donor kidney transplant for end-stage renal disease (ESRD) secondary to focal segmental glomerulosclerosis (FSGS). This patient received PD for 7 years but changed to hemodialysis (HD) in the year of transplant due to consistent signs and symptoms of underdialysis. EPS was visualized at the time of transplant. Despite successful renal transplantation, EPS progressed to cause small bowel obstruction (SBO) requiring PEG-J placement for enteral nutrition and gastric decompression. The patient subsequently developed a chronic gastrocutaneous fistula necessitating chronic TPN and multiple admissions for pain crises and bowel obstruction. He was elected to undergo surgical intervention due to deteriorating quality of life and failure to thrive. Surgical management included an exploratory laparotomy with extensive lysis of adhesions (LOA), repair of gastrocutaneous fistula, and end ileostomy with Hartmann’s pouch. Postoperative imaging confirmed resolution of the SBO, and the patient was transitioned to NGT feeds and eventually only PO intake. He is continuing with PO nutrition, gaining weight, and free from dialysis. Conclusion. Surgical intervention with LOA and release of small intestine can be successful for definitive management of EPS in the proper setting. In cases such as this, where management with enteral nutrition fails secondary to ongoing obstructive episodes, surgical intervention can be pursued in the interest of preserving quality of life.